Phase formation and electrical properties of SBNLT ceramics prepared via combustion technique - Sinkruason, Thanapon; Luangpangai, Anupong; Charoenthai, Nipaphat; Rittidech, Aurawan; Pulphol, Phieraya; Vittayakorn, Naratip; Bongkarn, Theerachai (My University, 2023)
This report investigates the effect of firing temperatures on the phase formation, microstructure, electrical, and energy storage properties of lead-free Sr0.3(Bi0.7Na0.67Li0.03)0.5TiO3 (SBNLT) ceramics, synthesised by combustion technique. The samples were calcined between 700°C and 900°C for 2 h and sintered between 1100°C and 1200°C for 2 h. The ceramics exhibited coexisting rhombohedral and tetragonal phases, which were confirmed by the Rietveld refinement technique. A morphotropic phase boundary (MPB) of the rhombohedral and tetragonal phases, with a ratio of 49:51, was obtained at the sintering temperature of 1175°C. The highest maximum dielectric constant (ε max= 4667), polarisation (P max= 28.80 µC/cm2) and energy density (W = 0.95 J/cm3), with a breakdown strength of 70 kV/cm, were achieved from the sample sintered at 1175°C.
Keywords: dielectric; ferroelectric; SBNLT; solid-state combustion